(untitled) (Acta Scientiarum. Biological Sciences, 2018)
The jatuarana (Brycon amazonicus), is an important species for the Madeira River commercial fisheries. The paper aims to characterize the jatuarana fishing dynamics in the middle Madeira River and test whether there are differences dowstreams and upstreams the Teotônio waterfall. Commercial fisheries landings were monitored daily at 15 ports or riverine communities along that stretch, using semi-structured interviews with fishermen. With data from the fishing monitoring program of UHEs Santo Antônio and Jirau we analysed: the yield, catch per unit effort (CPUE), length structure, locations and fishing gear used, between 2009 to 2011.The fishing yield of this species was temporaly analyzed with data from the Fishermen Colony of Porto Velho city (Rondônia state, Brazil), between 1990 to 2012. The yield and the CPUE showed significant differences by area and locations and the capture of the species was carried out primarily in the channel river and banks river through gillnets. In addition, the samples collected in the upstream area have higher distribution and modal lengths than from those collected downstream. These results suggest that the areas require distinct management measures.